Comparações genotípicas e fenotípicas de diferentes isolados clínicos de colonização e candidemia por Candida albicans - Santos, Fernanda Pahim [UNIFESP] (2009)
Introduction: Candida albicans is part of the human microbiota, but it can cause disseminated infection depending on the host immunity status. It is the most virulent species of the genus Candida as well as is frequently isolated from superficial and systemic infections. Some putative virulence factors have been recently proposed for C. albicans, including: adhesion to host epithelial and endothelial cells, the ability to secrete hydrolytic enzymes, yeast-to-hypha transition and the capability to combat oxidative stress generated by phagocytic cells Objectives: to characterize virulence attributes of different C. albicans clinical isolates; to analyze intraspecific genetic relatedness and to determine antifungal susceptibility of clinical isolates collected from a specific clinical scenario. Material and Methods: We have investigated 51 isolates sequentially obtained from 7 patients divided into 3 different groups: a) 3 patients who were only colonized (17 isolates); b) 3 colonized patients who had candidemia and were discharged (27 isolates); and c) 1 colonized patient who died of candidemia (7 isolates). We have investigated the following virulence factors: maximum growth rates, proteinase and phospholipase activity, adherence to human buccal epithelial cells, morphogenesis and biofilm formation. We also performed antifungal susceptibility testing by using broth microdilution method with amphotericin B, fluconazole, itraconazole, 5-fluorocytosine, caspofungin and anidulafungin. To investigate genetic variability, we have used a microsatellite technique with primer M13, followed by dendrogram construction, in addition to A, B, C genotyping. Results: We have found that all the isolates except strain 657B presented similar growth rates. The strains exhibited variable ability to adhere to buccal epithelia and to for hyphae. Therefore, we could not establish a direct relationship between these virulence attributes and patients clinical outcome. Strains obtained from patient 7, belonging to group III (candidemia/death) had the highest levels of proteinase activity, seconded by the isolates collected from patient 4 (candidemia/discharge). Phospholipase activity was essentially the same for all the isolates investigated in the present study, except from some patient 4 strains (candidemia/discharge) which were phospholipase negative. Isolates from patients 4 (candidemia/discharge), and 7 (candidemia/death) showed the highest levels of biofilm formation. We could not detect resistance to antifungal drugs among the isolates. However, a unique strain was DDS to 5-fluorocytosine (170 A). Microsatelite and A, B, C typing demonstrated that isolates from groups II and III (candidemia) showed lower genetic variability than the strains belonging to group I (only colonized). Conclusion: It was possible to verify that besides host immunity, each isolate had particular aspects which could be important factors to guarantee their success as pathogens. In addition, we emphasize the importance of molecular tools to detect genotypes well adapted to the human organism, which are likely responsible for worse prognosis in the hospital environment.